Household food insecurity among urban welfare recipient households in Hulu Langat, Selangor - Sulaiman, Norhasmah; Mohd Shariff, Zalilah; Kandiah, Mirnalini; Mohd Taib, Mohd Nasir; Abu Samah, Asnarulkhadi (Universiti Putra Malaysia Press, 2012)
Food insecurity is defined as a condition whenever people are not able to access enough food at all time for an active and healthy life, as well as the availability of adequate and safe food acquired by socially acceptable ways. This study utilized the Malaysian Coping Strategy Instrument (MCSI) to determine the percentage and the risk factors of food insecurity among the urban welfare recipient households in Hulu Langat, Selangor. A total of one hundred and three women (aged 20-55 years old) from selected welfare recipient households were involved in this study. Questionnaires were used to collect demographic and socio-economic information, as well as food security status of the participating households. The results indicated that 26.3% of the households faced food security, while 39.8% experienced moderate food insecurity, and 34.0% were subjected to severe food insecurity. The risk factors of food insecurity included the presence of children below 7 years old (F=3.690; p≤0.05), school-going children (F=2.599; p≤ 0.5), disabled members in the households (F=3.690; p<0.028), income reliance on financial assistance and per capita income (F=4.349; p≤0.05). In conclusion, food insecurity is a major public health problem among the urban welfare recipient households. Meanwhile, diverse risk factors were identified to have contributed to food insecurity in this study. Therefore, welfare recipient households with these circumstances ought to give priority to intervention programmes that address food insecurity by policy makers and programme implementers. In addition, the intervention programmes should be designed to address this issue and other risk factors influencing food acquisition.